Application of The Problem Based Learning Method Trought Authentic Assessment Approach to Improving the Habits of Mind - Moh Nurhadi; Ida Yayu Nurul Hizqiyah; Aas Saraswati (SAINTIS Publishing, 2019)
The purpose of this study is to improve the Habits of mind of students through the problem-based learning (PBL) model based on the otetic assessment of mathematics learning. The study was conducted on 39 students of class X. The research method used was an pre-experiment method. with One group pretest-posttest design. Data analysis carried out was Normality Test, Homogeneity Test, t Test, and N gain Test. The results of this study indicate that the application of authentic assessment-oriented PBL method can improve students' habit of mind in mathematics learning. This can be seen from the increasing results of assessment of creative thinking, and student self-regulated. the results of the creative thinking assessment are N-Gain values of 0.47 or included in the medium criteria and the results of the hypothesis test state that the significance is smaller than the reference sig it can be said that there are significant differences between the pretest and posttest values. The results of the assessment of self regulation, show the value of N gain 0.59 in the medium category so that it is said there is an increase between the value of the pretet results and the value of the posttest results.